2010
DOI: 10.1016/j.jcrs.2010.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes after wavefront-guided photorefractive keratectomy and wavefront-guided laser in situ keratomileusis: Prospective comparison

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 21 publications
4
35
1
3
Order By: Relevance
“…[1][2][3][4][5] On the other hand, photorefractive keratectomy (PRK) is now gaining renewed interest because wavefront-guided PRK induces changes directly on the first surface of the cornea. [6][7][8] Photorefractive keratectomy continues to be the most commonly performed corneal refractive surgery procedure in the United States Air Force and Navy for nonaviators and aviators. 9,10 The corneal wavefront aberration is not static but fluctuates over time.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] On the other hand, photorefractive keratectomy (PRK) is now gaining renewed interest because wavefront-guided PRK induces changes directly on the first surface of the cornea. [6][7][8] Photorefractive keratectomy continues to be the most commonly performed corneal refractive surgery procedure in the United States Air Force and Navy for nonaviators and aviators. 9,10 The corneal wavefront aberration is not static but fluctuates over time.…”
Section: Resultsmentioning
confidence: 99%
“…Outros estudos também tem demonstrado um aumento na indicação do PRK, já que essa técnica não apresenta complicações na confecção da lamela corneana, possuí menor risco de ectasia pós-ope ratória e resultados comparáveis ao LASIK (6)(7)(8)(9) .…”
Section: Discussionunclassified
“…Prior studies have shown that both wavefront-guided and wavefront-optimized PRK are effective and safe with similar outcomes compared with wavefront-based LASIK treatments [72][73][74].…”
Section: Wavefront-guided Versus Wavefront-optimized Photorefractive mentioning
confidence: 99%